2021
DOI: 10.3389/fmolb.2020.628551
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Interactions Between Heparin/Heparan Sulfate and SARS-CoV-2-Related Proteins—An Important Strategy for Developing Novel Therapeutics for the COVID-19 Pandemic

Abstract: Owing to the high mortality and the spread rate, the infectious disease caused by SARS-CoV-2 has become a major threat to public health and social economy, leading to over 70 million infections and 1. 6 million deaths to date. Since there are currently no effective therapeutic or widely available vaccines, it is of urgent need to look for new strategies for the treatment of SARS-CoV-2 infection diseases. Binding of a viral protein onto cell surface heparan sulfate (HS) is generally the first step in a cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 142 publications
(159 reference statements)
1
53
0
Order By: Relevance
“…A consistent amount of data supports the dependence of SARS-CoV-2 on HSPGs for an efficient infection. These data suggest that HSPGs serve as a co-receptor for the viral S protein interaction with the ACE2 entry receptor, thus contributing to viral internalization [ 66 , 109 , 110 , 129 , 132 , 225 ]. However, as HSPGs have been recognized as key inflammatory mediators in a variety of settings [ 6 , 226 , 227 ], they could play an important role in the regulation of the host cell immune response to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A consistent amount of data supports the dependence of SARS-CoV-2 on HSPGs for an efficient infection. These data suggest that HSPGs serve as a co-receptor for the viral S protein interaction with the ACE2 entry receptor, thus contributing to viral internalization [ 66 , 109 , 110 , 129 , 132 , 225 ]. However, as HSPGs have been recognized as key inflammatory mediators in a variety of settings [ 6 , 226 , 227 ], they could play an important role in the regulation of the host cell immune response to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2020, a substantial number of studies have addressed the role and the mechanisms underlying the interaction between the viral envelope S protein of SARS-CoV-2 and the HSPGs that provide the first anchoring sites for the virus on the host cell surface [ 66 , 81 , 129 , 130 , 131 , 132 ]. It has been established that the binding of the S protein of SARS-CoV-2 to the host cells requires the engagement of both HS and ACE2 [ 131 ], thus suggesting that HSPGs act as a co-receptor for the S protein interaction with the ACE2 entry receptor [ 66 ].…”
Section: Heparan Sulfate Proteoglycan Involvement In the Pathogenicity Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…During virus entry, SARS-CoV-2 spike protein was demonstrated to interact with both cellular heparan sulfate and ACE2 [ 16 ]. Therefore, disrupting the interaction between heparan sulphate and spike protein by exogenous and competitive heparin mimetics could limit the SARS-CoV-2 virus entering the cell, resulting in suppression of the inflammatory responses [ 98 ]. Histamine has been shown capable of binding to heparan sulfate [ 99 , 100 ].…”
Section: Potential Anti-sars-cov-2 Mechanisms Of H1 Receptor Antagonistsmentioning
confidence: 99%
“…HS shares high structural similarity with heparin, but their functionalities are differentiated by the interactions with various proteins, such as proteases and protease inhibitors, cytokines and their respective receptors [114]. Recently, the preclusion of interaction between HS and S protein from heparin/HS mimetics has been proposed like anti-SARS-CoV-2 drugs [58]. Furthermore, Tandon et al [59] also suggested that intranasal administration of unfractionated heparin could be used as a prophylactic treatment of SARS-CoV-2.…”
Section: Heparan Sulfatementioning
confidence: 99%